2008
DOI: 10.1371/journal.pone.0002993
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Melanin Response of the Soil Fungus Aspergillus niger to UV Radiation Stress at “Evolution Canyon”, Mount Carmel, Israel

Abstract: BackgroundAdaptation is an evolutionary process in which traits in a population are tailored by natural selection to better meet the challenges presented by the local environment. The major discussion relating to natural selection concerns the portraying of the cause and effect relationship between a presumably adaptive trait and selection agents generating it. Therefore, it is necessary to identify trait(s) that evolve in direct response to selection, enhancing the organism's fitness. “Evolution Canyon” (EC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 34 publications
6
84
0
Order By: Relevance
“…The adaptive melanin response of the soil fungus Aspergillus niger to UV radiation was clearly demonstrated in EC I (38). Mean conidial melanin concentration of 80 strains was threefold higher on the sunny AS than on the shady ES (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The adaptive melanin response of the soil fungus Aspergillus niger to UV radiation was clearly demonstrated in EC I (38). Mean conidial melanin concentration of 80 strains was threefold higher on the sunny AS than on the shady ES (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…We have begun a study of colony asymmetry in the soil fungus Aspergillus niger (Trichocomaceae: Ascomycota) from "Evolution Canyon." The conidia of populations on the south-facing slope have greater melanin content than do those on the north-facing slope [290]. This is presumably an adaptation to UV-stress on the exposed south-facing slope.…”
Section: Fungimentioning
confidence: 91%
“…24,25) This pigment, formed by oxidative polymerization of phenolic or indolic compounds, is not essential for fungal growth or development but has been reported to act as 'fungal armour' because of its ability to protect the microorganisms from harmful environmental conditions such as ultraviolet (UV) radiation, extreme temperatures, hydrolytic enzymes, heavy metal toxicity, and antimicrobial drugs. [25][26][27] Previously, we showed that melanin isolated from the MEL1 mutant of the fungus Aspergillus nidulans, which produces high levels of this pigment, is a potential hypochlorous acid scavenger and may be a promising component for cosmetic formulations that protect the skin against oxidative damage.…”
mentioning
confidence: 99%